Finding alternatives to disability benefit receipt - Gina Livermore; David Wittenburg; David Neumark (IZA Journal of Labor Policy, 2014)
This introduction offers a context for the articles in this thematic series by providing an overview of the programs that provide cash and in-kind supports to people with disabilities in the United States, summarizes the increasing reliance on these programs, and describes the challenges associated with reducing dependency on these programs. It then briefly discusses the articles in this thematic series in light of these issues.
Keywords: H5; I3; J2; J14; 330; Disability; Employment; Social Security Disability Insurance